Light stress diagnosis of rapeseed seedling stage based on hyperspectral imaging technology - WANG Yitian; ZHANG Xiaomin; JIANG Haiyi; ZHANG Yanning; LIN Yangyang; RAO Xiuqin (浙江大学学报. 农业与生命科学版, 2022)
Light stress can restrict the normal growth and development of rapeseed seedlings. In order to realize the early diagnosis of light stress in rapeseed seedlings, a 21 d experiment was conducted on rapeseed seedlings of two leaves and one heart stage using hyperspectral imaging technology. After preprocessing the collected canopy leaf spectra, the light-stress-sensitive bands were extracted through spectral reflectance and continuous wavelet transform. Then successive projection algorithm was used to extract characteristic wavelengths, and the continuous wavelet transform-stepwise discriminant analysis method was used to extract wavelet features. To further improve the accuracy of the stress detection model, a total of four features including the area under curve in the 939-978 nm band, the tangent value of the characteristic angle (tan θ), the reflectances at 984 and 1 408 nm were selected by analyzing the characteristics of the spectral band and the evolution of the spectral characteristics at the seedling stage of rapeseed to establish a multi-feature fusion Fisher discriminant model. The results showed that the average classification accuracy of the model was 86.88%, which achieved the best classification effect in the d20 family, with an accuracy of 95.00%. The research provides a powerful reference for the rapid diagnosis of light stress in rapeseed based on hyperspectral imaging technology.